Variant Termination of The Right Testicular Vein A Case Report - Syed, Abdi HM; Sah, Sanjay (Journal of Universal College of Medical Sciences, 2018)
This case report pertains to a variant termination of the right testicular vein into a large lower tributary of the right renal vein, instead of opening into the inferior vena cava. Since the lower vein in which the right testicular vein opened did not join the inferior vena cava directly, therefore there is no real duplication of the right renal vein which has been found in some previous case reports. The right renal vein had its normal termination into the inferior vena cava. Embryological explanation of the anomalous termination of the right testicular vein has been given. Journal of Universal College of Medical Sciences (2016) Vol.04 No.01 Issue 13, Page: 36-37